Answer:
3+(-3)
[+ × - = -]
3-3=0
15+(-3)
15-3=12
-3+(-3)
-3-3=-6
-9+(-3)
-9-3=-12
5/-1.21
[+ ÷ - = - ]
-1.21=-[121/100]
5/-[121/100]
5× -[100/121]
-[500/121]
-[4 16/121] or -[4.13](2 d.p)
-6/5÷1/3
-6/5×3/1
-18/5
-3.6
-8.4÷(-2.2)
- ÷ - = +
8.4÷2.2
84/10÷22/10
84/22
3.82(2d.p)
7/8÷(-1/6)
7/8 × -6/1
-42/8
-5.25
12×()= -180
make () the subject of formula by dividing both side by 12
()=-180/12
()= -15
()=(-11)-99
()=1089
-8×()=-168
()=-168/-8
()=21
()×(25)=-150
()=-150/25
()=-6
()×(-11)=99
()=99/-11
()=-9